Penerapan Pengendalian Kualitas Tempe pada Rumah Tempe Indonesia Kota Bogor - Veralianta Br Sebayang; Hanif Ash Shiddiq; Ainul Maisarah; Muh Ihsan Siddiq; Ahmad Izzan Raihannafi; Diaz Rizki Saputra (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze quality control in the tempe production process at Rumah Tempe Indonesia (RTI), Bogor, using the Seven Tools method. The data were collected through field observations, interviews with the production manager, and recording the types and quantities of defects over a one-month periode in February 2026. The analysis identified four main types of defects, namely overcooked, damaged packaging. spoiled tempe, and yellowing tempe, with a total of 353 defective products. Based on the Pareto diagram, overcooked tempe and damaged packaging were found to be the dominant defects, contributing to more than 70% of total defects. The scatter diagram analysis indicates that production volume does not have a strong relationship with the defect rate, suggesting that defects can still occur under both high and low production conditions. Meanwhile, the control chart shows that the production process is not yet fully under statistical control. Furthermore, the fishbone diagram analysis reveals that the causes of defects are influenced by several factors, including human, method, material, environment, and machine. This study recommends improving supervision during fermentation and packaging processes, as well as enhancing quality recording systems to improve overall product quality.